Implementasi Website Desa Untuk Mengoptimalkan Pelayanan Surat Pengantar dan Kritik Saran Terhadap Masyarakat Desa Kiringan - Shaniapuri, Alvin Risma; Yuniarfi, Irna; Manganti, Aprilia; AL-Ayyubi, Farras Raihan; Widago, Nugroho Adi (JURNAL PILAR TEKNOLOGI : Jurnal Ilmiah Ilmu Ilmu Teknik, 2020)
Abstract— Kiringan Village in serving its community has the objective of improving the welfare of rural communities and the quality of human life as well as reducing poverty through meeting basic needs, building village facilities and infrastructure, developing local economic potential, and utilizing natural and environmental resources in a sustainable manner. The community needs an optimization of public services in submitting cover letters which are still done manually. The Kiringan village office really needs a web-based information system that contains various kinds of information that can be accessed by the community including web profiles, important village information and supporting features for online correspondence. The use of a computerized system is expected to facilitate the community as users. In this study using the waterfall method. The arrangement of these methods is analysis, system design, implementation and testing. The results of this study are two kinds of users, namely User and Admin. The testing phase in this study uses blackbox testing. From the results of the tests that have been done, it is found that the features on the website are appropriate and easy to use. Keywords—: Public Service; Waterfall; Website.